PENGEMBANGAN POTENSI DESA MELALUI KEGIATAN AGROWISATA SAWAH DI KABUPATEN DELI SERDANG DALAM MENINGKATKAN EKONOMI DESA - Falahi, Adrial; Handayani, Leni (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2023)
Developing village potential through agrotourism activities is one of the effective strategies in improving the economy of rural communities. This study aims to analyze the potential and development of rice field agrotourism in Deli Serdang Regency and its impact on the village economy. The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation studies. The results of the study indicate that rice field agrotourism has great potential in attracting tourists, creating business opportunities, and increasing local community income. In addition, support from the local government, community participation, and good management are key factors in the success of this agrotourism development. Thus, the development of rice field agrotourism can be a model for village development based on sustainable local potential, so as to encourage economic growth and community welfare in Deli Serdang Regency.